Marfan Syndrome with Atypical Presentation: A Case Report (BIRDEM Medical Journal, 2014)
Marfan syndrome is an inherited connective tissue disorder that is transmitted as an autosomal dominant trait. These cases can be diagnosed by molecular cytogenetic techniques. A modified Ghent criteria using systemic scoring system can also identify these cases in absence of molecular cytogenetic techniques.We report a case of a 6 year 5 month old boy who presented with the complaints of excessive sweating sinceinfancy and protrusion of both eye balls which was non progressive since early childhood. On examination, some skeletal features of Marfan syndrome was found and echocardiogram showed huge dilatation of root of aorta which helped in diagnosis by scoring system.Birdem Med J 2014; 4(2): 111-114